2013
DOI: 10.3892/br.2013.110
|View full text |Cite
|
Sign up to set email alerts
|

Drug-loaded nano-microcapsules delivery system mediated by ultrasound-targeted microbubble destruction: A promising therapy method

Abstract: Abstract. The nano-microcapsules drug delivery system is currently a promising method for the treatment of many types of diseases, particularly tumors. However, the drug delivery efficiency does not reach a satisfactory level to meet treatment demands. Therefore, the effectiveness of delivery needs to be improved. Based on the alterations in the structure and modification of nano-microcapsules, ultrasound-targeted microbubble destruction (UTMD), a safe physical targeted method, may increase tissue penetration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Ultrasound microbubble-activation therapies have attractive features, including the ability to guide the treatment using ultrasound imaging, and real time feedback from the microbubble emissions (Cochran et al 2011; Kooiman et al 2014; Vignon et al 2013). Prospective treatments range from transient opening of capillaries, such as the blood brain barrier (Burgess and Hynynen, 2014), to complex methods for drug or gene delivery using specially prepared gaseous delivery vehicles that can be targeted to the desired region for treatment (Ma et al 2013). These methods have been studied for treatments such as gene therapy, cancer treatment, and thrombolysis (Laing and McPherson 2009; Ibsen et al 2013b; Unger et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound microbubble-activation therapies have attractive features, including the ability to guide the treatment using ultrasound imaging, and real time feedback from the microbubble emissions (Cochran et al 2011; Kooiman et al 2014; Vignon et al 2013). Prospective treatments range from transient opening of capillaries, such as the blood brain barrier (Burgess and Hynynen, 2014), to complex methods for drug or gene delivery using specially prepared gaseous delivery vehicles that can be targeted to the desired region for treatment (Ma et al 2013). These methods have been studied for treatments such as gene therapy, cancer treatment, and thrombolysis (Laing and McPherson 2009; Ibsen et al 2013b; Unger et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that local administration of cytotoxic agents with sonoporation is a useful method for molecular cancer therapy.The patient will be saved from adverse effects of anticancer drugs which usually act as double edged swords. 2,4 The confirmation of the delivery of compound into cells was made by using markers such as plasmid GFP. Some research focused on the study of sonoporation mechanisms in order to achieve optimal delivery outcome such as high delivery efficiency and minimal cell death.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Although clinical treatment is generally accomplished with surgery in those cases, the prognosis is not particularly good and the use of antiproliferative agents, such as 5-fluorouracil, mitomycin C and BLM, has been reported to remarkably improve the therapeutic effect. 4 Sonoporation efficiency is also related to the microbubble concentration and composition, as well as to the microbubble to cell ratio. 5,14,15 Additional therapy guided with sonoporation dramatically inhibited primary tumour growth throughout the course of the disease, with median survival increases of up to 10% demonstrated in adenocarcinomas of pancreatic xenografts in comparison to the control groups.…”
Section: Other Application In Dentistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The microparticle system extends the drug circulation time in the body and improves the drug concentration in target tissues. This increases the therapeutic efficacy and reduces the frequency of drug administration (6).…”
Section: Introductionmentioning
confidence: 99%